90 a.s.o. - Auvers-Sur-Oise. (Paris : MInistère de la Culture, 1990)
Boezem, Marinus ; Bruder, Pat ; Cano, Eugène ; Castellano, Gennaro ; George, Eric ; Gonzalez, Curro ; Huber, Stephan ; Joubert, Laurent ; Kleerebezem, Jouke ; Koether, Jutta ; Marek, Raoul ; Rondo, Julio ; Widoff, Anders
90 a.s.o. - Auvers-Sur-Oise, Auvers-Sur-Oise, 20 mai - 30 juin 1990
boek